2018
DOI: 10.1016/j.electacta.2018.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Liquid water saturation and oxygen transport resistance in polymer electrolyte membrane fuel cell gas diffusion layers

Abstract: In this thesis, the relative humidity (RH) of the cathode reactant gas was investigated as a factor which influences gas diffusion layer (GDL) liquid water accumulation and mass transport-related efficiency losses over a range of operating current densities in a polymer electrolyte membrane (PEM) fuel cell. Limiting current measurements were used to characterize fuel cell oxygen transport resistance while simultaneous measurements of liquid water accumulation were conducted using synchrotron X-ray radiography.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 131 publications
2
29
0
Order By: Relevance
“…Overall, the findings revealed that the electrolyte distribution inside the electrode is the key element for understanding the electrochemical performance. Therefore, in situ measurements of a working silver-based GDE should be carried out revealing the electrolyte distribution, as it has been already done for carbonbased GDE used in fuel cells [29]. These measurements are presently carried out in our research groups and will be reported in a forthcoming paper.…”
Section: Resultsmentioning
confidence: 95%
“…Overall, the findings revealed that the electrolyte distribution inside the electrode is the key element for understanding the electrochemical performance. Therefore, in situ measurements of a working silver-based GDE should be carried out revealing the electrolyte distribution, as it has been already done for carbonbased GDE used in fuel cells [29]. These measurements are presently carried out in our research groups and will be reported in a forthcoming paper.…”
Section: Resultsmentioning
confidence: 95%
“…As the name suggests, the voltage loss in the Ohmic region is typically considered to be dominated by ionic and electronic losses. However, it has been shown that an increase in cell compression increases the mass transport resistance in the Ohmic region which leads to the accumulation of liquid water in the MEA, amplifying the voltage loss [9,65]. The radiographs presented in Figure 5 compare the galvanostatic cell performances at both compressions in the Ohmic region (j = 0.6 A cm -2 ).…”
Section: Ohmic Regionmentioning
confidence: 99%
“…Several visualization techniques have been employed to investigate the liquid water distribution in perforated GDLs such as neutron radiography [21][22][23], environmental scanning electron microscope (ESEM) [24,25] and synchrotron X-ray radiography [26][27][28][29][30]. Lu et al [21] employed high resolution neutron radiography to visualize the liquid water distribution in GDLs with laser perforation.…”
Section: Introductionmentioning
confidence: 99%